2006
DOI: 10.1177/107110070602700801
|View full text |Cite
|
Sign up to set email alerts
|

Syndesmosis Fixation: A Comparison of Three and Four Cortices of Screw Fixation Without Hardware Removal

Abstract: The data suggest that either three or four cortices of fixation can be used when stabilizing syndesmotic injuries of the ankle. There was a trend towards higher loss of reduction in the group with tricortical fixation when weightbearing restrictions were not followed. Retention of the syndesmotic screws, even with mechanical failure, does not pose a clinical problem. Weightbearing can be allowed at 6 to 10 weeks without routine removal of screws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(90 citation statements)
references
References 28 publications
1
82
0
7
Order By: Relevance
“…1). Therefore, 12 studies were finally included [23][24][25][26][27][28][29][30][31][32][33][34] and are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Therefore, 12 studies were finally included [23][24][25][26][27][28][29][30][31][32][33][34] and are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Moore et al [28] reported that three cortical fixation was associated with more loss of reduction occurrence and contributed to its inadequate fixation strength. However our data analysis found neither significant difference of loss of reduction nor total complication incidence between the two methods.…”
Section: Discussionmentioning
confidence: 99%
“…No advantage of the tricortical method over the quadricortical one, 3.5 mm screws over 4.5 mm screws, flexible over rigid fixation or a specific timing of hardware removal has been found. The foot position during the fixation does not seem to be of clinical importance, either [21][22][23][24]. These findings were reflected in the survey results.…”
Section: Discussionmentioning
confidence: 96%
“…Nie udo wod nio no prze wagi ze spo leń trój ko ro wych nad czte ro ko ro wy mi, śrub o śred ni cy 3,5 nad 4,5 mm, ze spo leń ela stycz nych nad sztyw ny mi, cza su usu nię cia śrub wię zo zro stowych. Ta kże po zy cja sto py pod czas ze spa la nia wię -zo zro stu wy da je się nie mieć zna cze nia kli nicz ne go [21][22][23][24]. Zna la zło to od zwier cie dle nie w wy ni kach an kie ty.…”
Section: Discussionunclassified
“…a larger screw is stronger and easier to remove due to its large head, but there is no biomechanical advantage of a 4.5-mm screw over a 3.5-mm screw (thompson andGesink 2000, beumer et al 2005). a biomechanical study demonstrated that two syndesmosis screws could make a stronger construct than a single screw (Xenos et al 1995), three cortical syndesmosis screws allow some fibular movement and may not break or loosen compared to four screw cortices saltzman 2001, beumer et al 2005), but three or four cortices of fixation can be used to stabilize syndesmosis injuries (Moore et al 2006, Wikeroy et al 2010. previously, stability comparable to a tricortical 3.5-mm screw was achieved with two Kirchner wires (peter et al 1994), and it has been suggested that bioabsorbable syndesmosis screws are well tolerated and avoid the need for subsequent screw removal (thordarson et al 2001, hovis et al 2002).…”
Section: Mechanism Of Injury and Classificationmentioning
confidence: 99%